Nonlinear relationship between circulating homocysteine and parathyroid hormone among patients with osteoporotic fractures: A cross-sectional study based on a hospital cohort - Jia-Hao Wang; Wei-hong Wang; Da-wei He; Ke Lu; Chong Li; Yan-ming Hao (PLoS ONE, 2026)
Osteoporotic fractures are frequent among older adults and are often accompanied by disturbances in endocrine and metabolic regulation. Parathyroid hormone (PTH) serves as a key regulator of bone remodeling, while elevated plasma homocysteine—an established marker of vascular injury and skeletal fragility—has been implicated in osteoporosis. Yet, the interaction between these two biochemical factors remains insufficiently characterized. This study investigated the link between circulating homocysteine and serum PTH concentrations among 2,190 hospitalized patients with osteoporotic fractures, emphasizing nonlinear associations and modifying influences. Fasting blood samples obtained at admission were used to measure plasma homocysteine and intact PTH levels. Multiple regression and spline-based modeling techniques were employed to estimate independent relationships and potential threshold effects, with subgroup analyses considering hypertension, renal function, and magnesium status. Homocysteine demonstrated an independent, positive correlation with PTH (P < 0.001). A nonlinear dose–response relationship was observed, wherein PTH increased progressively with homocysteine up to about 18 μmol/L, followed by a sharper rise beyond this point, suggesting a statistically significant threshold. The relationship was more evident among patients with hypertension, impaired renal function, or low magnesium levels, indicating that vascular strain, renal stress, and mineral imbalance may heighten PTH activity. Elevated homocysteine levels may be associated with higher PTH concentrations in individuals with osteoporosis. However, the clinical relevance of homocysteine in metabolic assessment and risk stratification requires further validation.